Taxonomy and Learning Objectives - Nasrullah, Nasrullah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
ABSTRACT Learning is a process of interaction between educators and students and learning resources in an environment that exchanges information and assistance from educators to provide new knowledge, resulting in a process of acquiring knowledge and knowledge, mastery of skills and morals as well as self-confidence in students and supporting students. in order to study well. There are various aspects in a learning process, namely learning methods and media that can support learning to run smoothly. However, the terpentng in a process of learning is the goal of learning itself. The purpose of learning is the behavior of learners who want to achieve or hope that can be done in accordance learning competencies of learners after learning takes place. The description above shows how important a learning objective is in teaching and learning activities that can affect the success or failure of the learning process. The learning objectives become a reference for determining the type of material, learning strategies, learning methods and learning media that will be used in the learning process. Without a clear purpose, learning will be learning without direction, without focus, and become ineffective. Furthermore, the author also discusses the benefits of learning objectives, the extent to which the benefits of formulating learning objectives for educators and students, and discusses the scope of learning objectives such as cognitive, affective and psychomotor aspects. Then it ends with how to formulate good learning goals. Kata Kunci: Learning Objectives, Advantages, Scope.